Single atom alloy catalysts for C-H bond activation and propane dehydrogenation - Wimble, Joshua. (2017)
Abstract: Single atom alloys (SAAs) have shown considerable promise as heterogeneous catalysts for a wide range of industrially important reactions, by providing atomically dispersed active species to enable near 100% atom efficiency in catalytic systems. These materials are explored in this thesis for C-H bond activation reactions, which have become increasingly relevant in recent years as crude oil production in the US has become lighter due to increases in shale oil production. Single atom platinum, palladium, and nickel in the surfaces of supported copper nanoparticles were prepared by galvanic replacement for comparison to their monometallic nanoparticle counterparts in C-H bond activation reactions in butane and propane. As part of this work, deactivation kinetics were compared, for the first time, between single atom Pt, Pd, and Ni in Cu nanoparticles and their monometallic nanoparticle counterparts. The PtCu- and PdCu-SAAs were shown to have superior coke resistance when compared to Pt and Pd nanoparticles under realistic propane dehydrogenation conditions in a fixed bed reactor. For our reactions, we demonstrated that coke production rates are reduced by more than 90% in PdCu- and PtCu-SAAs. Deactivation mechanisms considered for PtCu- and PdCu-SAAs were most consistent with particle sintering and subsurface metal atom diffusion, while their monometallic equivalents were more consistent with deactivation by coking. Similar results were found for the C-H bond activation in butane, tested by H-D exchange over a range of temperatures. Additionally, reaction rates were measured for each system, and the apparent activation energies, Eapp, were calculated. These measurements were performed approximately at steady-state, but on partially deactivated catalysts. The extent of deactivation due to carbon deposition was different among the three metals. The Eapp were similar between single atom alloys and monometallic catalysts in contrast to DFT calculations performed elsewhere, showing that SAA catalysts should have higher Eapp . Eapp were as follows: for Pt and PtCu = 77±3 and 68±9 kJ/mol; for Pd and PdCu = 30±2 and 35±5 kJ/mol; and for NiCu-SAAs 17±5 kJ/mol. The reason for the different apparent activation energies between Pt and Pd is attributed to pore closure by carbon deposition in the latter. Excessive coking and very low reaction rates made calculation of activation energies over monometallic Ni nanoparticles impractical for our system. This is the first time that ambient pressure catalytic measurements in propane dehydrogenation were made for this series of bimetallic single atom catalysts, allowing for comparison between expected DFT trends and actual experimental data. This type of work will allow rational catalyst design to further refine the understanding of materials needed to allow access to low cost fine chemicals produced from olefins.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Maria Flytzani-Stephanopoulos.; Committee: Charles Sykes, and Prashant Deshlahra.; Keyword: Chemical engineering.